'Feeling for' and 'feeling with': developmental and neuroscientific perspectives on intersubjectivity and empathy. Issue 4 (9th September 2013) - Knox, Jean
Abstract: This paper discusses research by Beatrice Beebe, Bessel van der Kolk and others, exploring the interpersonal processes that underpin early relational trauma and how this contributes to adult psychopathology. An essential feature of early relational trauma, the infant's experience of being unable to evoke an empathic response from the caregiver and the feelings of shame this gives rise to, is discussed and its implications for psychotherapy are considered. The neuroscience that underpins two forms of empathy in the therapeutic relationship, of 'feeling for' and 'feeling with' the patient is discussed and explored in relation to the concordant and complementary countertransference. I argue that when therapists respond to the projection on to them of the abuser by an increasingly determined adherence to analytic technique, this may become a complementary countertransference identification with the abuser and an enactment of the abusive relationship.